2017
DOI: 10.18632/oncotarget.16145
|View full text |Cite
|
Sign up to set email alerts
|

NID1, a new regulator of EMT required for metastasis and chemoresistance of ovarian cancer cells

Abstract: Nidogen-1 (NID1) has been identified as a novel candidate diagnostic biomarker of ovarian cancer in our previous study. Nevertheless, the role of NID1 in the pathogenesis of ovarian cancer is unclear. In the present study, we demonstrated that NID1 was a mesenchymal associated gene and its high expression was significantly correlated with shorter overall survival of ovarian cancer patients. The ectopic expression of NID1 in OVCAR-3 cells revealed a epithelial-mesenchymal transition (EMT) phenotype accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…Thus, NID1 has been shown to promote tumor cell migration, invasion, and chemoresistance in ovarian carcinomas via the induction of Epithelial-Mesenchymal Transition (EMT). 66 Another study revealed a possible NID1 involvement in the acquisition of migratory and invasive properties by endometrial cancer cells. 67 It has also been shown that NID1 was present at high levels in the secretome of lung metastases in both breast cancer and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NID1 has been shown to promote tumor cell migration, invasion, and chemoresistance in ovarian carcinomas via the induction of Epithelial-Mesenchymal Transition (EMT). 66 Another study revealed a possible NID1 involvement in the acquisition of migratory and invasive properties by endometrial cancer cells. 67 It has also been shown that NID1 was present at high levels in the secretome of lung metastases in both breast cancer and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…As a secreted pro-metastatic protein, NID1 has been reported to promote lung metastasis of breast cancer and melanoma 35 . Zhou et al 20 also showed that NID1 promoted EMT of ovarian cancer cells through activating extracellular-signal-regulated kinase/mitogen-activated protein kinase signaling. Here, in our study, JQ1 obviously reduced the mRNA and protein expression of NID1 in all GC cells and NID1 was necessary for JQ1-inducing suppression of GC cell migration and invasion validated by rescue experiments.…”
Section: Discussionmentioning
confidence: 98%
“…4e). Among the 40 mostly dysregulated genes upon JQ1 treatment, we chose NID1 as the target gene, because NID1 has been reported to promote cancer metastasis in various cancer types 20 (Fig. 4f).…”
Section: Jq1 Significantly Reduces the Expression Of Nid1 In Gc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a serious disease particularly when it is in its advanced stages with a course that is punctuated by frequent tumour recurrence and negative impact on quality and length of life [1]. Despite enormous efforts, there are no successful screening methods developed until now to decrease mortality, whether by pelvic examination, ultrasonography or by use of serum markers.…”
Section: Introductionmentioning
confidence: 99%